M-FUZZY h-IDEALS IN h-SEMISIMPLE M-Γ-HEMIRINGS - Pan, Deng; Shan, Jianming; Kim, Hee Sik (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper, the concepts of M-fuzzy h-interior ideals and prime M-fuzzy h-ideals in M-Γ-hemirings are introduced. Some new properties of these kinds of M-fuzzy h-ideals are also given. Finally, some characterizations of the h-semisimple M-Γ-hemirings are investigated by these kinds of M-fuzzy h-ideals.